Education university challenge - Solano Zuñiga, Iván (2012)
The students are in college to specialize and learn to be individuals.This way for people to last a lifetime,looking for a perfection that we can not reach,but sought in an effort to be better every day. For this, we must commit ourselves and with others, in which the teacher commitmentis on our side.We need a set of principles and values ​​that govern our daily existence, that constitute ourways.In college we face a different kind of education the school. We need to becomeowners of the subject, and "squeeze" the teacher, whichmust lead by example for us to joinlearn the cause. We must realize thatWe can not achieve our goal being mediocre students.It requires that we "all" of us accepting strengths and weaknesses, always seekingbecome the "ideal person".In education must look each time with acritical eye. We should not think of graduate and become working machines, try to be people, education and drive of the university gives usthe possibility of achieving something that not many achieve.